Alterations of amino acids in older adults with Alzheimer’s Disease and Vascular Dementia - Xin Ma; Xin-Meng Wang; Guo-Zhang Tang; Yi Wang; Xue‑Chun Liu; Shuai-Deng Wang; Peng Peng; Xiu-Hong Qi; Xin-Ya Qin; Yue‑Ju Wang; Chen-Wei Wang; Jiang-Ning Zhou (Amino Acids)
Abstract Metabolomics provide a promising tool for understanding dementia pathogenesis and identifying novel biomarkers. This study aimed to identify amino acid biomarkers for Alzheimer’s Disease (AD) and Vascular Dementia (VD). By amino acid metabolomics, the concentrations of amino acids were determined in the serum of AD and VD patients as well as age-matched healthy controls. Several differences in the concentration of amino acids were observed in AD patients compared to both healthy controls and VD patients. However, no significant distinction was found between healthy controls and VD patients. Considering comorbidities, cystine levels were higher in AD than in VD among non-diabetic patients, but not in those with diabetes. Notably, creatine, spermidine, cystine, and tyrosine demonstrated favorable results in decision curve analyses and good discriminative performances, suggesting their potential for clinical application. These fundings give novel perspectives of serum amino acids for predicting metabolic pathways in AD and VD pathogenesis.